Diagnostic of visceral leishmaniasis by polymerase chain reaction PCR in experimental mice infected which treatment with Viscum album extract and Pentostam. - Maksood A.M. Al-Doori; Tawfiq I . Al-Alousi; Abdulla H. Al-Jboori (Tikrit Journal of Pure Science, 2023)
Visceral leishmaniasis (VL), or kala-azar, is an infection of the reticuloendothelial system, Fatalities due to leishmaniasis are associated with visceral disease. the  Leishmaia donovani   is a causative agent for this disease. In the current study, white male mice of the Balb /C strain were experimentally infected with the leishmania donovani promastigotes  and were then treated with a Viscum extract and compared with the Pentostam. The aim of this study was to evaluate the sensitivity and specificity of polymerase chain reaction (PCR) in the detection of Leishmania DNA in blood samples of infected mice. as well as, evaluation the ability of Viscum album extract to treatment the visceral leishmaniasis. The genetic study gave excellent results in the diagnosis of infection throughout the treatment period compared to the positive and negative control . Using  the specific LdI primer , the 700bp of the parasite was diagnosed. This Broad band was shown in the positive control samples, in the pantostam treatment groups, and the muscular injection with viscum extract in the first 15 days and in the   oral dosage  group in the first 20 days of initiation. While the band  did not appear in any other. The current study has shown promising results in the use of V. album in the treatment of visceral leishmaniasis and also gave impressive results in the diagnosis of infection PCR.